LPJ-GUESS Peatland: Modeling of Pan-arctic Peatland Carbon Dynamics Under Different Warming Scenarios - Chaudhary, Nitin; Zhang , Wenxin; Lamba, Shubhangi; Westermann, Sebastian (Research Advances in Environment, Geography and Earth Science Vol. 4, 2024)
Peatlands are considered one of the biggest carbon reserves in the terrestrial ecosystem, comprising 30% of the present-day soil organic carbon pool. Peatlands store large amounts of carbon in terrestrial ecosystems and they are vulnerable to recent warming. The ongoing warming may change their carbon sink capacity and could reduce their potential to sequester carbon. Peatland carbon dynamics in distinct future climate conditions using the peatland-vegetation model were simulated here. The study examined whether less pronounced warming could further enhance the peatland carbon sink capacity and buffer the effects of climate change. LPJ-GUESS (Lund-Potsdam-Jena General Ecosystem Simulator) is a second-generation dynamic global vegetation model (DGVM) that is widely employed in global carbon cycle and vegetation dynamics studies. Using this model, this study has performed experiments with four major RCP warming scenarios such as RCP2.6, RCP4.5, RCP6.0, and RCP8.5. This study also determined which trajectory peatland carbon balance would follow, what the main drivers were, and which one would dominate in the future. It is found that peatlands will largely retain their carbon sink capacity under the climate scenario RCP2.6 to RCP6.0. According to the simulations of this study, permafrost peatland fractions are predicted to reduce to 41%, 35.8%, 35.7%, and 28% under RCP2.6, RCP4.5, RCP6.0, and RCP8.5 respectively. Peatlands are projected to shift from a carbon sink to a carbon-neutral (5–10 gC m -2 yr -1) in RCP8.5. Higher respiration rates will dominate the net productivity in a warmer world leading to a reduction in carbon sink capacity.